2011
DOI: 10.1007/jhep12(2011)051
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical strings in marginally deformed toric AdS/CFT

Abstract: We study string solutions in the β-deformed Sasaki-Einstein gauge/gravity dualities. We find that the BPS point-like strings move in the submanifolds where the two U(1) circles shrink to zero size. In the corresponding T 3 fibration description, the strings live on the edges of the polyhedron, where the T 3 fibration degenerates to T 1 . Moreover, we find that for each deformed Sasaki-Einstein manifold the BPS string solutions exist only for particular values of the deformation parameter. Our results imply tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…We also note that we would expect the baryon analysis in β-deformed Sasaki-Einstein manifolds to provide similar results to the undeformed case. Our string and brane configurations do not seem to depend strongly on the deformation in the way encountered in [39], where important modifications due to the deformation appeared only in the T 3 fibration description.…”
Section: Discussionmentioning
confidence: 68%
“…We also note that we would expect the baryon analysis in β-deformed Sasaki-Einstein manifolds to provide similar results to the undeformed case. Our string and brane configurations do not seem to depend strongly on the deformation in the way encountered in [39], where important modifications due to the deformation appeared only in the T 3 fibration description.…”
Section: Discussionmentioning
confidence: 68%
“…It would be interesting to investigate the deformed gravity duals of these backgrounds on a wider swath of phase space, including non-integrable trajectories. The prototypical background is furnished by Sasaki-Einstein manifolds: AdS 5 ×Y p,q [51], where the method applied here can be used by generalizing the string solutions obtained in [52]. The un-deformed backgrounds are already known to be non-integrable [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The string solutions again show chaotic behavior implying nonintegrability of the corresponding sigma models. However, in Y p,q manifolds special care should be taken with the string solution to show that indeed they satisfy the Sasaki-Einstein constraints as in [15,16,17]. More recently it has been shown that integrability is not present in marginal complex β-deformations [18].…”
Section: Introduction and Methodsmentioning
confidence: 99%